ODARRL: Obstacle- and Disturbance-Aware End-to-End Residual Reinforcement Learning for Underwater Robot Trajectory Tracking with Obstacle Avoidance - Linghan Meng; Zebin Huang; Qingfeng Yao; Yunxiu Zhang; Qifeng Zhang (Journal of Marine Science and Engineering, 2026)
ROVs are essential for marine exploration and underwater operations, yet conventional teleoperation relies heavily on skilled human operators, and many autonomous methods stop at high-level planning rather than low-level actuation, limiting robustness in disturbed and cluttered environments. This paper proposes ODARRL, an obstacle- and disturbance-aware sensor-to-thruster (ST) end-to-end residual reinforcement learning framework for safe trajectory execution of underwater robots. Using a three-stage curriculum, ODARRL first acquires a basic policy from MPC demonstrations in a static obstacle-free environment, then improves disturbance-robust tracking under random currents, and finally extends to scenarios involving both currents and obstacles. A Dual-Horizon Attention Disturbance Encoder is further designed to capture current-related features from long- and short-term histories, which are fused with robot states and reference information as the input to the ST end-to-end policy. Experiments in Marine Gym with BlueROV2 Heavy demonstrate that ODARRL achieves more stable and robust trajectory tracking under random currents, reducing the mean total tracking error by 69.3%, 31.9%, 45.8%, 73.0% and 25.8% relative to the MPC-imitation policy, PPO, SAC, A2C and VNRS-SAC, respectively. With obstacles introduced, curriculum-initialized policies also exhibit higher path progress and more stable task completion during obstacle-avoidance training.

Penetration of benzotriazole ultraviolet stabilizers across the blood-cerebrospinal fluid barrier in patients with leptomeningeal metastasis - Yuxiang Weng; Chi Hu; Meng Wang; Zebin Fang; Feng Xiao; Luyuan Zhang; Chao Zhang; Ping Lan; Yu Zhu; Kaiyuan Huang (Journal of Hazardous Materials, 2026)

Subfamily I ethylene receptors are functionally conserved in calcium permeability across the green lineage - Dongsheng Yu; Chuanli Ju; Zebin Liu; Changxin Feng; Yu Wang; Yujia Sun; Lei Gao; Chunyan Li; Enjie Yu; Xuan He; Haimei Su; Mengchen Hu; et al. (Molecular Plant, 2026)

The embodied agricultural NH3 emissions in China's inter-provincial trade and the implied environmental inequities - Lu Lu; Zebin Zhao; Jinpan Jiang; Fan Meng; Ziyi Wang; Changshun Wang; Jingchao Li; Hong Qi; Donglei Fu (Journal of Cleaner Production, 2025)

Nitrate addition in different anoxic stages of acid paddy soil and the impacts on cadmium immobilization - Hanbing Meng; Shan Wang; Yang Yang; Zebin Hong; Shiwen Hu; Guojun Chen; Kuan Cheng; Tongxu Liu (Chemical Geology, 2025)

Neuroprotective effect of Licochalcone A against aluminum chloride-induced neurotoxicity by reducing Aβ accumulation, oxidative stress and inflammatory reaction - Zhijuan Tang; Fang Wang; Jintao Lv; Gaohong Yang; Xinchun Shen; Fei Zeng; Lingling Meng; Wen Zhou; Libin Zhan; Zebin Weng (NeuroToxicology, 2025)

Effects of zero-valent iron added in the flooding or drainage process on cadmium immobilization in an acid paddy soil - Hanbing Meng; Shiwen Hu; Zebin Hong; Wenting Chi; Guojun Chen; Kuan Cheng; Qi Wang; Tongxu Liu; Fangbai Li; Kexue Liu; Yang Yang (Journal of Environmental Sciences, 2024)

Estimation of water quality variables based on machine learning model and cluster analysis-based empirical model using multi-source remote sensing data in inland reservoirs, South China - Di Tian; Xinfeng Zhao; Lei Gao; Zuobing Liang; Zaizhi Yang; Pengcheng Zhang; Qirui Wu; Kun Ren; Rui Li; Chenchen Yang; Shaoheng Li; Meng Wang; et al. (Environmental Pollution, 2024)

A 1-aminocyclopropane-1-carboxylate deaminase MrACCD from Metarhizium robertsii is associated with plant growth promotion for Metarhizium spp - Xinggang Liao; Qian Luo; Chao Wu; Dan Zhou; Jianfeng Li; Zebin Meng (Journal of Invertebrate Pathology, 2023)